2011
DOI: 10.1016/j.ejvs.2010.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Expression of Toll-like Receptor 4 in Peripheral Blood of Ischaemic Stroke Patients Correlates with Cyclooxygenase 2 Expression

Abstract: Our results suggest that the peripheral mechanism of inflammatory injury after stroke may be mediated by TLR4 through a COX-2-dependent pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Most NSAIDs inhibit the activity of cyclooxygenase (COX)-1 and −2, and downstream synthesis of prostaglandins. It has been observed that COX-2 is increased in the blood of ischemic stroke patients (Ferronato et al, 2011). Also in the case of NSAIDs most studied have been focused on neuroprotection and the acute and subacute phases of microglia-mediated events.…”
Section: Other Pharmacological Modulations Of Inflammatory Signalimentioning
confidence: 99%
“…Most NSAIDs inhibit the activity of cyclooxygenase (COX)-1 and −2, and downstream synthesis of prostaglandins. It has been observed that COX-2 is increased in the blood of ischemic stroke patients (Ferronato et al, 2011). Also in the case of NSAIDs most studied have been focused on neuroprotection and the acute and subacute phases of microglia-mediated events.…”
Section: Other Pharmacological Modulations Of Inflammatory Signalimentioning
confidence: 99%
“…This leads to the degradation of inhibitor of kappa B (I κ B) and the triggering translocation of nuclear factor- κ B (NF- κ B) into the nucleus, which induces the production of proinflammatory cytokines such as interleukin-1 β (IL-1 β ), IL-6, and tumor necrosis factor- α (TNF- α ) [11]. Clinical studies have reported that the expression levels of TLR2 and TLR4 in peripheral blood in the acute stage are related to the severity and prognosis of patients in the following stage [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…11 Controls were individuals presenting no sign of atherosclerotic plaques at ecodoppler examination. DNA and total RNA were extracted from peripheral blood samples.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical severity of stroke was rated through the National Institute of Health Stroke Scale (NIHSS). 12 Functional polymorphisms À1607T4C, À2026A4G and À2604G4A 13 were genotyped by PCR-restriction fragment length polymorphism (Supplementary Table 2), and gene expression was performed by Real-time PCR as described 11 (Supplementary Table 3). By in silico analysis, other single-nucleotide polymorphisms present in the region do not alter transcriptionbinding sites or are in strong linkage disequilibrium with the selected ones.…”
Section: Resultsmentioning
confidence: 99%